Multi-Parametric Delineation Approach for Homogeneous Sectioning of Asphalt Pavements - Naga Siva Pavani Peraka; Krishna Prapoorna Biligiri; Satyanarayana N. Kalidindi (Engineering Proceedings, 2023)
Maintenance of homogeneous road sections is one of the approaches to economizing the overall management of pavement systems. The objective of this study was to develop a multi-parameter-based delineation approach to segmenting the pavements into subsections in a way that considers multiple pavement characteristics. Deflection bowl parameters, pavement functional performance, surface layer modulus, and traffic were analyzed to develop a multi-parametric delineation index (MPDI), which was used in C-charts-based segmentation to obtain homogeneous sections. Importantly, the segmentation processes were automated using a deep neural network designed for rational implementation by practitioners. The devised approach was found to be efficient in segmenting the pavements, selecting the sections that are in direst need of maintenance, and necessitating prompt response from the agencies.